Association of Equiliberative Nucleoside Transporter (ENT) with liver fibrosis stage in Hepatitis-C - Furqan Bhatti; Binafsha Manzoor Syed; Ikram Din Ujjan (Journal of the Pakistan Medical Association, 2022)
Abstract Objective: To evaluate the pattern of equiliberative nucleoside transporters in viral hepatitis responding and non-responding patients, to correlate the liver fibrosis stage with the pattern among the non-responders, and to correlate the equiliberative nucleoside transporter status with housekeeping hypoxanthine-guanine phosphoribosyltransferase gene. Method: The comparative cross-sectional study was conducted at the Molecular Biology and Genetics Department, Liaquat University of Medical and Health Sciences, Jamshoro, Pakistan, from March to August 2018, and comprised adult hepatitis C virus patients of either gender who completed six months of treatment. They were assessed for response to therapy in terms of the presence of the viral load in their serum by using real time polymerase chain reaction, and divided into responder group A and non-responder group B. The groups were compared and correlation between equiliberative nucleoside transporter expressions and liver fibrosis was evaluated. Data was analysed using SPSS 23. Results: Of the 80 patients, 33(41.3%) were males and 47(58.8%) were females. The overall mean age was 37.46±10.61 years. In terms of response to treatment, there were 40(50%) in each of the two groups. Mean post-treatment duration was 15.38±30.09 weeks. Age was not significantly different with respect to gender (p>0.05), but the age pattern was significantly different between the two groups (p<0.001). Also, non-responders had significant post-treatment duration compared to the responders (p<0.001). Hypoxanthine-guanine phosphoribosyltransferase gene showed no significant difference between the groups (p=0.144). —Continue